Honeymoon Tourism as Romantic Consumption in China - Weiqi Yan; Junmin Liu; Yujie Zhu (Via@)
This article explores the rise of honeymoon tourism in China, a modern phenomenon inspired by Western influences that amalgamates wedding celebrations and tourism. By examining the sociocultural changes associated with honeymoon tourism across the past four decades, this study explores the motivations behind this tourism and its implications for Chinese society. Honeymoon tourism is a microcosm of modern China’s quest for romantic consumption. Inspired by the framework of 'rites of passage,' this study shows that honeymoon travel reveals newly married couples' interest in separating from their original families and their search for extraordinary rather than mundane experiences. These intentions, either reflexive or embodied, lead to the consumption of various romanticised practices and products, including photos, celebratory rituals and vlog-making. As an active embrace of modern consumerism, these cultural products symbolise a collective impetus to seize and monumentalise love relationships through the ‘tourism moment’. In so doing, honeymoon tourism as romantic consumption in China is not simply a hedonistic search for a romantic experience but a cultural response to rapid modernisation and sociocultural changes.